Black hole scaling relations of active and quiescent galaxies: Addressing selection effects and constraining virial factors. Issue 1 (7th February 2019) - Shankar, Francesco; Bernardi, Mariangela; Richardson, Kayleigh; Marsden, Christopher; Sheth, Ravi K; Allevato, Viola; Graziani, Luca; Mezcua, Mar; Ricci, Federica; Penny, Samantha J; La Franca, Fabio; Pacucci, Fabio
Abstract: Local samples of quiescent galaxies with dynamically measured black hole masses ( M bh ) may suffer from an angular resolution-related selection effect, which could bias the observed scaling relations between M bh and host galaxy properties away from the intrinsic relations. In particular, previous work has shown that the observed M bh – M star relation is more strongly biased than the M bh –σ relation. Local samples of active galactic nuclei (AGN) do not suffer from this selection effect, as in these samples M bh is estimated from megamasers and/or reverberation mapping-based techniques. With the exception of megamasers, M bh estimates in these AGN samples are proportional to a virial coefficient f vir . Direct modelling of the broad-line region suggests that f vir ∼ 3.5. However, this results in an M bh – M star relation for AGN, which lies below and is steeper than the one observed for quiescent black hole samples. A similar though milder trend is seen for the M bh –σ relation. Matching the high-mass end of the M bh – M star and M bh –σ relations observed in quiescent samples requires f vir ≳ 15 and f vir ≳ 7, respectively. On the other hand, f vir ∼ 3.5 yields M bh –σ and M bh – M star relations for AGN, which are remarkably consistent with the expected 'intrinsic' correlations for quiescent samples (i.e. once account has been made of the angular resolution-related selection effect), providing additional evidence that the sample of local quiescent black holes is biased. We also show that, as is the case for quiescent black holes, the M bh – M star scaling relation of AGN is driven by σ, thus providing additional key constraints to black hole–galaxy co-evolution models.